2011
DOI: 10.1159/000330359
|View full text |Cite
|
Sign up to set email alerts
|

Relative Size of Auditory Pathways in Symmetrically and Asymmetrically Eared Owls

Abstract: Owls are highly efficient predators with a specialized auditory system designed to aid in the localization of prey. One of the most unique anatomical features of the owl auditory system is the evolution of vertically asymmetrical ears in some species, which improves their ability to localize the elevational component of a sound stimulus. In the asymmetrically eared barn owl, interaural time differences (ITD) are used to localize sounds in azimuth, whereas interaural level differences (ILD) are used to localize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 154 publications
2
32
0
Order By: Relevance
“…Comparing cluster dendrograms with a phylogeny of the species of interest can reveal whether interspecific variation is largely attributable to phylogenetic relatedness or to some ecological or behavioral factor(s) [Iwaniuk and Hurd, 2005]. This approach has been widely used in comparative studies of avian neuroanatomy [Rehkamper et al, 2003;Iwaniuk and Hurd, 2005;Iwaniuk et al, 2006;Gutiérrez-Ibáñez et al, 2011], including studies on the visual system [Partridge, 1989;Hart, 2001]. We compared cluster dendrograms to the owl phylogeny studied by Wink et al [2008], which represents the most complete molecular phylogeny for owls currently available.…”
Section: Cell Soma Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing cluster dendrograms with a phylogeny of the species of interest can reveal whether interspecific variation is largely attributable to phylogenetic relatedness or to some ecological or behavioral factor(s) [Iwaniuk and Hurd, 2005]. This approach has been widely used in comparative studies of avian neuroanatomy [Rehkamper et al, 2003;Iwaniuk and Hurd, 2005;Iwaniuk et al, 2006;Gutiérrez-Ibáñez et al, 2011], including studies on the visual system [Partridge, 1989;Hart, 2001]. We compared cluster dendrograms to the owl phylogeny studied by Wink et al [2008], which represents the most complete molecular phylogeny for owls currently available.…”
Section: Cell Soma Areamentioning
confidence: 99%
“…For these owls, the visual horizon is at least partially obscured by vegetation and/or darkness and so presumably does not represent a major component of the perceived worlds of these species. The northern saw-whet, barred, great grey and barn owls have some degree of ear asymmetry and auditory nuclei enlargement, suggesting that they might rely more upon auditory cues than other owls [Norberg, 1977;Gutiérrez-Ibáñez et al, 2011]. For example, barn owls and great grey owls are capable of capturing prey in the total absence of visual cues [Nero, 1980;Takahashi, 2010].…”
Section: Retinal Topography and Activity Pattern And Habitatmentioning
confidence: 99%
“…On the basis of Bravo and Pettigrew's [1981] results, we expect differences in the relative size of the thalamofugal pathway, between diurnal and nocturnal species and/or between strigid and tytonid owls. Finally, we have recently shown that asymmetrically eared owls have enlarged auditory pathways when compared to symmetrically eared ones [Gutiérrez-Ibáñez et al, 2011]. Several studies in mammals [Eisenberg, 1981;Baron et al, 1996;Barton, 1998;Catania, 2005] have shown that trade-offs can occur between different sensory systems, and species that rely heavily on one sensory modality (with a corresponding enlargement of associated brain areas) have relatively smaller brain regions dedicated to other sensory modalities.…”
Section: Introductionmentioning
confidence: 83%
“…Beach et al [1987] suggested that formaldehyde can only penetrate 1-2 mm in tissue blocks, but formaldehyde can, in fact, penetrate much deeper than that, provided that the specimens are left in the fixative for an extended period of time [Fox et al, 1985]. Indeed, immersion fixation can yield high-quality specimens for measuring brain region volume, cytoarchitecture and immunohistochemistry [Iwaniuk and Wylie, 2007;Iwaniuk et al, 2009;Gutiérrez-Ibáñez et al, 2011;Corfield et al, 2012] even for large brains [Hof et al, 2000;Manger et al, 2003;Wang et al, 2008;Raghanti et al, 2009].…”
Section: Brain Specimens and Histologymentioning
confidence: 99%
“…The proportional sizes of the brain regions were also examined through the use of hierarchical cluster analysis [Rehkamper et al, 2003;Iwaniuk and Hurd, 2005;Gutiérrez-Ibáñez et al, 2011]. The proportional sizes of the four main brain regions, telencephalon, optic lobes, cerebellum and brainstem, or the telencephalic regions (see above) were included.…”
Section: Statistical Analysesmentioning
confidence: 99%